Improving mental health through parenting programmes: block randomised controlled trial. Issue 6 (1st December 2002) - Patterson, J; Barlow, J; Mockford, C; Klimes, I; Pyper, C; Stewart-Brown, S
Abstract : Aims: To assess the effectiveness of a parenting programme, delivered by health visitors in primary care, in improving the mental health of children and their parents among a representative general practice population. Methods: Parents of children aged 2–8 years who scored in the upper 50% on a behaviour inventory were randomised to the Webster-Stratton 10 week parenting programme delivered by trained health visitors, or no intervention. Main outcome measures were the Eyberg Child Behaviour Inventory and the Goodman Strengths and Difficulties Questionnaire to measure child behaviour, and the General Health Questionnaire, Abidin's Parenting Stress Index, and Rosenberg's Self Esteem Scale to measure parents' mental health. These outcomes were measured before and immediately after the intervention, and at six months follow up. Results: The intervention was more effective at improving some aspects of the children's mental health, notably conduct problems, than the no intervention control condition. The Goodman conduct problem score was reduced at immediate and six month follow up, and the Eyberg Child Behaviour Inventory was reduced at six months. The intervention also had a short term impact on social dysfunction among parents. These benefits were seen among families with children scoring in the clinical range for behaviour problems and also among children scoring in the non-clinical (normal) range. Conclusion: This intervention could make a useful contribution to the prevention of child behaviour problems and to mental health promotion in primary care.